Metodología para el Diseño de Conjuntos Difusos Tipo-2 a partir de Opiniones de Expertos - Rodríguez Ayala, Mónica Lorena; Huertas Moreno, Yeniffer Estefanía (Ingeniería, 2016)
Context: There is a need for processing information coming from human like language that includes uncertainty in order to solve problems defined in that context. Method: We use Type-2 fuzzy sets for defining and measuring human like language, so we propose a methodology for designing them. The proposal is composed by three key steps: (1) defining a linguistic label (word), (2) defining its membership function, and (3) collecting information from experts. Results: The proposal is applied and validated in a real scenario based on triangular fuzzy sets through two different groups of experts. We present a proposal to model, process and analyze input information coming from experts that allows to do an appropriate handling of uncertainty present in people perceptions. Conclusions: The proposed methodology is applicable to different problems where different people express their opinions and/or perceptions about a specific problem.